Manufacturing in the digital age - Pradhan, Mohan Kumar; Gaikwad, Mahendra U.; Shanmugam, Ragavanantham (Advanced materials processing and manufacturing, 2025)
This book covers manufacturing in the current context of Industry 4.0 and the impending era of Industry 5.0 exploring the path established by the manufacturing sector including developments, constraints, difficulties, and solutions. The importance of sustainability in the manufacturing sector, particularly in the context of Industry 4.0, is the focus. The difficulties in implementing Industry 4.0 and Industry 5.0 and providing advice on how to get past these barriers are also discussed including sustainable methods and approaches to deal with environmental issues. Covers robotics, IoT, additive manufacturing, sustainability, and machine learning for productivity and quality in digital age manufacturing Includes case studies based on real world aspects and research and innovations in the field of digitalization and optimization of manufacturing Covers sustainability interventions in the digital age manufacturing Explains product design and development in the era of Industry 4.0 and 5.0 Reviews data management and policy-based aspects This book is aimed at researchers and graduate students in mechanical, industrial, and production engineering.